Goodbye, Brazil : émigrés from the land of soccer and samba - Margolis, Maxine L., 1942- (University of Wisconsin Press, 2013)
Brazil, a country that has always received immigrants, only rarely saw its own citizens move abroad. Beginning in the late 1980s, however, thousands of Brazilians left for the United States, Japan, Portugal, Italy, and other nations, propelled by a series of intense economic crises. By 2009 an estimated three million Brazilians were living abroad -- about 40 percent of them in the United States. This book provides a global perspective on Brazilian emigration. Drawing and synthesizing data from a host of sociological and anthropological studies, a preeminent Brazilian immigration scholar surveys and analyzes this greatly expanded Brazilian diaspora, asking who these immigrants are, why they left home, how they traveled abroad, how the Brazilian government responded to their exodus, and how their host countries received them.